Enterprise Restructuring in Transition: A Quantitative Survey - Djankov, Simeon; Murrell, Peter (Journal of Economic Literature, 2002)
We survey the empirical literature analyzing the process of enterprise restructuring in transition economies. The survey provides new insights into the relative effectiveness of different reform policies, and into how this effectiveness varies across regions. We study the effects of privatization, the importance of different types of owners, the effects of foreign and domestic competition, the consequences of soft budgets, and the role of managerial incentives and managerial human capital, with regard to enterprise restructuring.